2019
DOI: 10.30552/ejihpe.v9i2.324
|View full text |Cite
|
Sign up to set email alerts
|

El impacto del apoyo social y la inteligencia emocional percibida sobre el rendimiento académico en Educación Secundaria

Abstract: El apoyo social (familia, profesorado y grupo de iguales), así como la percepción que tienen los individuos de sus habilidades emocionales podrían ser factores que condicionasen el rendimiento académico en Educación Secundaria, aunque la evidencia empírica no es del todo concluyente. El objetivo de este estudio es examinar la influencia directa de las principales fuentes de apoyo social y de la inteligencia emocional percibida sobre el rendimiento académico del alumnado de Educación Secundaria Obligatoria y Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…On a practical level, the results of the current study point, in the first place, to the support of the effectiveness of programmes aimed to enhance EI levels [50]. Moreover, an increase of EI improves, to a large extent, the teachers' self-efficacy, because when emotional abilities are used with success, this fact provokes a better teacher performance [27], and teachers become a solid social support for students [51].…”
Section: Limitations and Future Research Linessupporting
confidence: 56%
“…On a practical level, the results of the current study point, in the first place, to the support of the effectiveness of programmes aimed to enhance EI levels [50]. Moreover, an increase of EI improves, to a large extent, the teachers' self-efficacy, because when emotional abilities are used with success, this fact provokes a better teacher performance [27], and teachers become a solid social support for students [51].…”
Section: Limitations and Future Research Linessupporting
confidence: 56%
“…Several studies have indicated that there is a significant relationship between perceived emotional intelligence (PEI) and school performance in secondary school [ 66 , 67 , 68 ]. Antonio-Aguirre et al [ 69 ] indicate that the only dimension of the PEI that seems to affect academic performance is emotional attention—the negative effect is limited, and its influence is also limited to the female gender. In other words, paying too much attention to emotions would contribute toward enhancing ruminative thinking, placing personal and school adjustment at risk [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents spend most of their daily time in the classroom, have to face new and complex school tasks, and deal with different kinds of pressure and expectations [36]. In light of the emotional burden related to overwhelming school demands and the abovementioned evidence, it is not surprising that they are significantly influenced by the emotional support received from significant adults in the school environment [14,37,38]. Teacher emotional support refers to a teacher's ability to create positive relationships with their students and promote their autonomy and socioemotional functioning [14,39].…”
Section: The Mediating Role Of Perceived Teacher Emotional Supportmentioning
confidence: 99%